Autoimmune liver disease : management and clinical practice - 4 0 16; Neuberger, James,;Hirschfield, Gideon M.; 5 (Hoboken, NJ : Wiley-Blackwell, 2020)
Autoimmune Liver Disease discusses the current understanding about autoimmune liver diseases, focusing on pathogenesis, diagnosis and management. The first section covers the current immunological thinking about autoimmunity and focus on liver diseases with emphasis on the spectrum, significance, use and abuse of autoantibodies and on the implications of the recent advances in the genetics of autoimmunity to allow the reader to place these exciting developments in context. The second section describes four main hepatic autoimmune liver diseases and follows a common format that focuses on aspects of diagnosis and management. Liver transplantation plays an important role in treatment so timing and outcomes are covered: recurrence of autoimmune liver disease is important not only for the recipient and their clinicians but also sheds light on the pathogenesis. De novo autoimmune hepatitis is included in both clinical and scientific chapters. Finally, the authors treat three areas where experience has shown there is uncertainty. The final chapter includes reference to optimal approaches to patient management, including patient empowerment. To ensure that the whole clinical spectrum of autoimmune liver disease is covered, each chapter is jointly covered by contributing authors who are clinicians caring for adult, transitional and paediatric patients--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; Diseases;Immunological aspects. -- Liver;Autoimmune diseases. -- 20; 20; 2